Недостатність юридичної визначеності спрощеного позовного провадження - Андронов, Ігор Володимирович; Андронов, І. В.; Andronov, Ihor V. (Херсон : Видавничий дім «Гельветика», 2019)
У статті викладено наукові результати аналізу положень нової редакції Цивільного процесуального кодексу України та надано оцінку норм, які визначають порядок віднесення цивільних справ до категорії малозначних та призначення цивільних справ до розгляду в порядку спрощеного позовного провадження, з точки зору їх відповідності принципу юридичної визначеності. Сформульовано пропозиції щодо вдосконалення правового регулювання спрощеного позовного провадження з метою усунення суперечливості норм процесуального закону.

The article presents the scientific results of the analysis of the provisions of the new version of the Civil Procedure Code of Ukraine and provides an assessment of the norms, that determine the procedure for assigning civil cases to the category of insignificant and assigning civil cases to consideration in the order of simplified claim proceedings, in terms of their compliance with the principle of legal certainty. It is established that the term «insignificant matter» enshrined in the procedural law has nothing to do with the true assessment of the meaning of the case for the court or the parties. The impartiality of the court, in particular, means that it has an equal attitude to every case in its proceedings, and therefore no case can be of greater or lesser importance to it. As regards the value of the case to the parties, especially the claimant, it is not objectively assessed. The insignificance of a case is a legal characteristic of a case that has entirely objective criteria, the presence or absence of which is judged by the court. The criteria for classifying cases as insignificant, first of all, depend on whether the claims are property in nature, that is, the price of the claim. It is argued that the use by the legislator of the evaluation category of «case of insignificant complexity» as a criterion for referring a case to insignificant negatively affects the legal certainty of this issue. The existence of a link between the recognition of a case of insignificant nature and the order of its consideration (in summary proceedings) gives grounds to argue that cases of insignificant complexity should be recognized, in particular, cases that do not require a preparatory hearing. It is a matter of a fair, impartial and timely hearing, and the decisions of which can be secured without committing procedural actions by the court in preparatory proceedings. Also, the legal problem that a court must resolve when considering a case should not be too complicated. As a rule, this applies to cases in which a settled case law of their consideration has already been formed, in particular, existing legal opinions of the Supreme Court in similar cases regarding the application of the rules of law to be applied. Proposals for improvement of the legal regulation of the simplified lawsuit are formulated in order to eliminate the contradictions of the rules of procedural law.
Андронов І. В. Недостатність юридичної визначеності спрощеного позовного провадження / І. В. Андронов // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Херсон : Видавничий дім «Гельветика», 2019. – Вип. 34. – С. 17-22.
Keywords: правосуддя; цивільний процес; малозначні справи; принципи права; позовне провадження; справа незначної складності; юридична визначеність; justice; civil process; minor cases; principles of law; claim proceedings; small-scale case; legal certainty; Research Subject Categories::LAW/JURISPRUDENCE